Bagasse-based co-generation at Hippo Valley Estates sugar factory in Zimbabwe - Mtunzi, Busiso; Mampwheli, tshengedzeni; Meyer, Edson; Mungwena, Wilson (Journal of Energy in Southern Africa, 2017)
The paper reports on the assessment of the use of bagasse for cogeneration purposes at Hippo Valley Estates (HVE), a sugar manufacturing company in Zimbabwe. Much emphasis was on an assessment of the quantity of energy that was lost due to inefficient combustion of bagasse and the use of steam that was generated. The study investigated the quantity of sugar cane processed and the possible corresponding steam produced; the sugarcane processed was found to be approximately 2.33 million tons per annum and the steam produced was 193.1 tons per hour. The steam was used in the process department as well as to drive mills. The excess steam generated was found to be 81.03 tons per hour. Economic analysis on the use of excess steam to produce extra power for sale to the utility company was also undertaken. It was established that the power plant for the company could generate an annual surplus of US2.8Million as revenue, and the payback period was found to be 3.3 years. The sensitivity analysis of the project indicated that the electricity prices as well as the energy produced were the most sensitive areas in the project. The other inputs such as operations and maintenance costs, interest, capital investment and number of years were not as sensitive as the price and the energy.